Omentin-1 enhances the inhibitory effect of endothelial progenitor cells on neointimal hyperplasia by inhibiting the p38 MAPK/CREB pathway - Xiang, Yuan; Zhou, Zhengshi; Zhu, Lingping; Li, Chuanchang; Luo, Ying; Zhou, Jipeng (Life sciences (1973), 2023)
Endothelial progenitor cells (EPCs) play an important role in vascular repair. However, they are dysfunctional in the inflammatory microenvironment during restenosis. In this study, we investigated whether omentin-1, an anti-inflammatory factor, could reduce neointima formation after carotid artery injury (CAI) in rats by improving EPC functions that were damaged by inflammation and the underlying mechanisms. EPCs were transfected with adenoviral vectors expressing human omentin-1 or green fluorescent protein (GFP). Then, the rats received 2 × 106 EPCs expressing omentin-1 or GFP by tail vein injection directly after CAI and again 24 h later. Hematoxylin-eosin staining and immunohistochemistry were used for analyzing neointimal hyperplasia. Besides, EPCs were treated with omentin-1 and TNF-α to examine the underlying mechanism. Our results showed that omentin-1 could significantly improve EPC functions, including proliferation, apoptosis and tube formation. Meanwhile, EPCs overexpressed with omentin-1 could significantly reduce neointimal hyperplasia and tumor necrosis factor-α (TNF-α) expression after CAI in rats. TNF-α could notably induce EPC dysfunction, which could be markedly reversed by omentin-1 through the inhibition of the p38 MAPK/CREB pathway. Furthermore, a p38 MAPK agonist (anisomycin) significantly abrogated the protective effects of omentin-1 on EPCs damaged by TNF-α. Our results indicated that genetically modifying EPC with omentin-1 could be an alternative strategy for the treatment of restenosis. [Display omitted]